The Preconceptions of Children at a Preschool Age on the Topic of the Air and the Weather - Rochovská, Ivana (Multidisciplinary Journal of School Education, 2015)
This paper is focused on the preconceptions of children at a preschool age on the topic of the air and the weather. The aim of the paper is to identify and describe the given preconceptions, to further analyse and interpret them and, on the basis of this, to propose investigative activities which would develop these preconceptions of the children. A structured interview was used as the method to knd out the preconceptions among the children.